THE ROLE OF MEDIA AND INFORMATION SERVICES IN SPORTS EVENTS: PRESS SERVICE, INTERNATIONAL EXPERIENCE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the significance of media and information services in sports events. The role of television, sports news, and special projects in promoting physical education and a healthy lifestyle is highlighted. Furthermore, the article demonstrates how the effective operation of press services contributes to improving the organizational level of competitions.